Regional Integration and Informal Trade in Africa: Evidence from Benin's Borders. (19th July 2018) - Bensassi, Sami; Jarreau, Joachim; Mitaritonna, Cristina
Abstract: Regional trade is low in sub-saharan Africa. But a large share of regional trade is informal, i.e., not recorded in official data. This paper studies the relationship between trade barriers and informality of trade. We use an original survey of informal transactions across Benin's land borders, which provides the first direct and comprehensive account of trade volumes and product coverage for this type of trade. We combine this data with official trade records and exploit variation across products and countries to measure the impact of tariff and non-tariff barriers to trade on informality. Increasing tariffs on a given product by 10% makes it about 12% more likely that this product is imported informally rather than formally. Non-tariff measures also increase informality. Our results also suggest that compliance costs, aside from tariffs and regulations, contribute to explain informality.